Dissection of Anti-tumor Activity of Histone Deacetylase Inhibitor SAHA in Nasopharyngeal Carcinoma Cells via Quantitative Phosphoproteomics - Huang, Huichao; Fu, Ying; Zhang, Ye; Peng, Fang; Lu, Miaolong; Feng, Yilu; Chen, Lin; Chen, Zhuchu; Li, Maoyu; Chen, Yongheng (Frontiers in Cell and Developmental Biology, 2020)
Suberoylanilide hydroxamic acid (SAHA), a pan HDAC inhibitor, has been approved by FDA to treat cutaneous T cell lymphoma. Nevertheless, the mechanisms underlying the therapeutic effects of SAHA on tumors are yet not fully understood. Protein phosphorylation is one of the most important means to regulate key biological processes, such as cell division, growth, migration, differentiation, and intercellular communication. Thus, investigation on the impacts of SAHA treatment on global cellular phosphorylation covering major signaling pathways deepens our understanding on its anti-tumor mechanisms. Here we comprehensively identified and quantified protein phosphorylation for the first time in nasopharyngeal carcinoma (NPC) cells upon SAHA treatment, by combining tandem mass tags (TMT)-based quantitative proteomics and titanium dioxide-based phosphopeptide enrichment. Totally, 7430 phosphorylation sites on 2456 phosphoproteins were identified in the NPC cell line 5-8F, of which 1176 phosphorylation sites on 528 phosphoproteins were significantly elevated upon SAHA treatment. Gene ontology analysis showed that SAHA influenced several biological processes including mRNA/DNA processing and cell cycle. Furthermore, signaling pathway analysis and immunoblotting demonstrated that SAHA activated tumor suppressors like p53 and Rb1 via phosphorylation and promotes cell apoptosis in NPC cells, but inactivated energetic pathways such as the AMPK signaling. Overall, our study indicated that SAHA exerted anti-tumor roles in NPC cells, which may serve as a novel therapeutic for NPC patients.